Relationship between glucose homeostasis and obesity in early life—a study of Italian children and adolescents. Issue 5 (30th September 2021) - Balkhiyarova, Zhanna; Luciano, Rosa; Kaakinen, Marika; Ulrich, Anna; Shmeliov, Aleksey; Bianchi, Marzia; Chioma, Laura; Dallapiccola, Bruno; Prokopenko, Inga; Manco, Melania
Abstract: Epidemic obesity is the most important risk factor for prediabetes and type 2 diabetes (T2D) in youth as it is in adults. Obesity shares pathophysiological mechanisms with T2D and is likely to share part of the genetic background. We aimed to test if weighted genetic risk scores (GRSs) for T2D, fasting glucose (FG) and fasting insulin (FI) predict glycaemic traits and if there is a causal relationship between obesity and impaired glucose metabolism in children and adolescents. Genotyping of 42 SNPs established by genome-wide association studies for T2D, FG and FI was performed in 1660 Italian youths aged between 2 and 19 years. We defined GRS for T2D, FG and FI and tested their effects on glycaemic traits, including FG, FI, indices of insulin resistance/beta cell function and body mass index (BMI). We evaluated causal relationships between obesity and FG/FI using one-sample Mendelian randomization analyses in both directions. GRS-FG was associated with FG (beta = 0.075 mmol/l, SE = 0.011, P  = 1.58 × 10 −11 ) and beta cell function (beta = −0.041, SE = 0.0090 P  = 5.13 × 10 −6 ). GRS-T2D also demonstrated an association with beta cell function (beta = −0.020, SE = 0.021 P  = 0.030). We detected a causal effect of increased BMI on levels of FI in Italian youths (beta = 0.31 ln (pmol/l), 95%CI [0.078, 0.54], P  = 0.0085), while there was no effect of FG/FI levels on BMI. Our results demonstrate that the glycaemic and T2D risk genetic variants contribute to higher FG and FI levels and decreased beta cell function in children and adolescents. The causal effects of adiposity on increased insulin resistance are detectable from childhood age.